2022
DOI: 10.3389/fgene.2021.809815
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Autosomal InDel Loci With Multiple Insertions or Deletions of Random DNA Sequences in Human Genome

Abstract: Multiple mutational events of insertion/deletion occurring at or around InDel sites could form multi-allelic InDels and multi-InDels (abbreviated as MM-InDels), while InDels with random DNA sequences could imply a unique mutation event at these loci. In this study, preliminary investigation of MM-InDels with random sequences was conducted using high-throughput phased data from the 1000 Genomes Project. A total of 3,599 multi-allelic InDels and 6,375 multi-InDels were filtered with multiple alleles. A vast majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…However, the distribution patterns of MM-InDel revealed their similar-ity in the human genome. It should be noted, however, that the presence of the additional alleles in MM-InDels was contingent upon the sequential occurrence of secondary mutational events during migration and expansion of the population [10]. Therefore, simultaneous utilization of both MM-InDels can considerably augment the number of candidate markers and provide higher efficiency for a multiplex assay.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the distribution patterns of MM-InDel revealed their similar-ity in the human genome. It should be noted, however, that the presence of the additional alleles in MM-InDels was contingent upon the sequential occurrence of secondary mutational events during migration and expansion of the population [10]. Therefore, simultaneous utilization of both MM-InDels can considerably augment the number of candidate markers and provide higher efficiency for a multiplex assay.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, MM‐InDels recognized for their high polymorphism across diverse populations were deliberately chosen. Moreover, the previous study has shown that there was a more frequent presence of adjacent InDel loci within a short distance of 20 bp, which indicates a potentially strong correlation between two InDels with an interval of less than 20 bp [10]. The first insertion or deletion mutation can be regarded as an important factor for the initiation of the secondary mutation event leading to the formation of such multi‐InDels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations